(untitled) - Vaughan, Tay (New York, 2008)
This book/CD package is a revision of our successful Multimedia: Making It Work. This edition is restructured for easier use and details the various stages of multimedia development. The book includes all the newest advancements in multimedia. A CD-ROM containing demo versions of all Macromedia authoring tools replace the Tempra software included with the first book, making this edition truly a Mac and Window's book. This is the most authoritative and comprehensive guide on multimedia, and it's being developed in cooperation with Macromedia, the central player in the multimedia authoring tools market, and the only multimedia company that offers development tools on the Mac and Windows.
Keywords: Multimedia systems